New Peptaibiotics and a Cyclodepsipeptide from Ijuhya vitellina: Isolation, Identification, Cytotoxic and Nematicidal Activities - Ashaimaa Y. Moussa; Christopher Lambert; Theresia E.B. Stradal; Samad Ashrafi; Wolfgang Maier; Marc Stadler; Soleiman E. Helaly (MDPI AG, 2020)
Fungal associations with nematodes have attracted scientific attention because of the need to develop new biocontrol agents. In this context, Ijuhya vitellina, an antagonistic fungus previously isolated from the plant parasitic cyst nematode Heterodera filipjevi, was selected to carry out an in-depth metabolomic study for its active metabolites. Herein, three new nonapeptide peptaibols with leucinostatin based sequences were isolated and identified by 1, 2D NMR, and HR-ESI-MS-MS. The absolute configuration was assigned based on Marfay’s analysis and Mosher ester formation. The new leucinostatins manifested moderate nematicidal effect against the plant pathogenic nematode Pratylenchus penetrans with LD90 values ranging from 5 to 7 µg/mL. Furthermore, a cyclodepsipeptide, named arthrichitin D, with five amino acid residues attached to a 3-hydroxy-2,4-dimethylhexadeca-4,6-dienoic fatty acid chain was discovered and showed weak nematicidal effect against Caenorhabditis elegans. Chaetoglobosin B and its 19-O-acetyl derivative were also obtained as minor metabolites, and the activity of chaetoglobosin B on the actin cytoskeleton of mammalian cells was assessed.